(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In Indian art, along with the various religious aspects of life, the temporal aspects have alsobeen shaped in a wide dimension. The collective experience and thoughts of the Indian society have beenexpressed in various mediums of art in architecture, sculpture and painting. . In Asian art, various forms ofdivine figures of fairies, gandhas and apsaras, represented by Brahmanical, Buddhist and Jain religions,have been formed.